An inventory model for deteriorating items under time varying demand condition - Mishra, Srichandan; Mishra, S.P.; Mishra, N.; Panda, J. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this paper we discuss the development of an inventory model for deteriorating items which investigates an instantaneous replenishment model for the items under cost minimization. A time varying type of demand rate with infinite time horizon, exponential deterioration and with shortage in considered. The result is illustrated with numerical example.